PRIMARY PULMONARY HODGKIN'S LYMPHOMA: RARE CLINICAL CASE - E.O. RODIONOV; S.V. MILLER; S.A. TUZIKOV; T.L. KRAVCHUK; L.N. BONDAR; U.B. URMONOV; O.V. SAVENKOVA (Avicenna Tajik State Medical University, 2018)
Lung involvement in Hodgkin's lymphoma (HL) occurs from 15% to 40% of cases. In most patients, it is caused by germination of the affected mediastinal lymphatic nodes in the lung parenchyma. Primary pulmonary form of Hodgkin's lymphoma is a rare disease: in the world literature for the period 1927- 2006 of all, more than 70 cases have been described. The main diagnostic criteria for the primary pulmonary form of HL are: 1) the disease should be limited to the with a minimal lesion of the pulmonary root lymph nodes or without it; 2) a typical histological picture of Hodgkin's lymphoma; 3) clinical and/or pathological exclusion of damage to other organs and lymph nodes. The article presents a clinical case of long-term observation and successful treatment of a 54-years-old patient with this disease.